PELATIHAN KINESIOTAPING SEBAGAI UPAYA PREVENTIF SPRAIN ANKLE ATLET MUDA IVOKAS - Yunitasari; Nasri; Nur Amin (PT. Saha Kreasi Indonesia, 2026)
Ankle injuries are a common problem among volleyball athletes, especially adolescents, due to the movement characteristics involving jumping, landing, and rapid changes of direction. Limited knowledge and skills in injury prevention at the club level increase the risk of recurrent injuries and may affect the sustainability of athletic performance. This community service activity aimed to improve the knowledge and skills of young athletes in the prevention and early management of ankle injuries through basic kinesiotaping training. A descriptive quantitative approach with a one-group pre-test and post-test design was applied in a single training session conducted on November 28, 2025, at Ivokas Volleyball Club, Semarang Regency, involving 12 young athletes. The training consisted of theoretical sessions, hands-on practice, and evaluation. The results showed an increase in the average knowledge score from 42.6 to 85.4, along with improved participant ability to apply basic kinesiotaping techniques, particularly lymphatic drainage and mechanical correction techniques for the ankle. In addition, participants reported very positive responses to the training implementation. It can be concluded that basic kinesiotaping training is effective in enhancing the knowledge and practical skills of young athletes in ankle injury prevention, and has the potential to support athlete safety and sustainable performance at the club level.